Zarathustra’s Philosafari - Traisnel, Antoine (Humanimalia, 2012)
This essay imagines Nietzsche’s Thus Spoke Zarathustra as a zoological excursion that maps a series of human-animal encounters in which the human is but one species among others. Zarathustra is the reader’s guide for this “philosafari,” as he appears to be an incarnation of “the acknowledging one [who] goes among men as among animals.” By seeing the human – but also the animal – as animal, Zarathustra proposes a revaluation of the epistemic pretensions of the human gaze. It is through spectatorial distance, I argue, that Nietzsche moderates the difficult relations between the humans and their animal relatives.